Proceedings of the 1st Indo-China research series in geotechnical and geoenvironmental engineering - Garg, Ankit; Solanki, C. H.; Bogireddy, Chandra; Liu, Junwei (Springer, 2021)
This book is a compilation of selected papers from the 1st Indo-China Research Series in Geotechnical and Geoenvironmental Engineering held in May 2020 online. The webinar series was held at a time of COVID-19 pandemic, when there is lack of physical connectivity. The cutting-edge research topics in Civil and Environmental Engineering ranging from bio-geotechnology, methane gas hydrates, frozen soils, rock testing, and related high-rise buildings response under wind loading will be covered. The contents make valuable contributions to academic researchers and engineers in the industry and provide a platform for demonstrating joint research between scientists from India and China. These are the first proceedings of its kind to demonstrate and motivate more joint research cooperation in Civil and Environmental Engineering between two countries. It was done mainly to motivate youth research scholars to understand each other and develop long-term cooperation.